PENGEMBANGAN MULTIMEDIA SHAPE FUN BERBANTUAN LAGU UNTUK MENINGKATKAN HASIL BELAJAR SEGI BANYAK SISWA SEKOLAH DASAR - Anisah Rasyidah; Putri Yanuarita Sutikno (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT This study was motivated by the low learning outcomes of fourth-grade students in mathematics lessons on polygons, due to the use of learning media that were not engaging or varied enough. This situation indicates the need for innovative, interactive learning media that are suited to the characteristics of elementary school students. This study aims to develop and determine the effectiveness of the song-assisted Shape Fun multimedia program in improving student learning outcomes. The method applied was research and development (R&D) using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were 25 fourth-grade students in the large group and 7 students in the small group. Data collection was conducted through observation, interviews, questionnaires, a small-scale test, and a large-scale test. Data analysis utilized the Shapiro–Wilk normality test, the Paired-Sample T-Test, and the N-Gain test. Multimedia Shape Fun was rated“highly recommended” by media experts and subject matter experts, with a score of 93.7%. This approval was granted because the Shape Fun multimedia program, which incorporates songs, features an engaging interface, user-friendly navigation, and a combination of text, images, interactive quizzes, and educational songs that are tailored to the characteristics of elementary school students. This multimedia program is effective, with a significance value of 0.000 and an N-gain value of 0.71—which falls into the “high” category—demonstrating a significant improvement in learning outcomes. These results indicate that the Shape Fun multimedia program, which incorporates songs as an innovative digital learning tool, is highly suitable and effective for improving the learning outcomes of fourth-grade students in mathematics lessons on polygons. ABSTRAK Penelitian ini didasari oleh rendahnya hasil belajar peserta didik kelas IV dalam pembelajaran matematika materi segi banyak, akibat penerapan media pembelajaran yang kurang menarik dan variatif. Keadaan tersebut mengindikasikan perlunya inovasi media pembelajaran yang interaktif dan sesuai dengan karakteristik peserta didik sekolah dasar. Penelitian ini bertujuan mengembangkan dan mengetahui efektivitas multimedia Shape Fun berbantuan lagu untuk meningkatkan hasil belajar peserta didik. Metode yang diterapkan yaitu dengan penelitian dan pengembangan (Research and Development) dengan model ADDIE yang mencakup tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Subjek penelitian ini yaitu  peserta didik kelas IV yang berjumlah 25 sebagai kelompok besar dan 7 peserta didik kelompok kecil. Pengumpulan data dilakukan dengan observasi, wawancara, kuesioner, uji skala kecil, dan uji skala besar. Analisis data menggunakan  uji normalitas Shapiro–Wilk, uji   Paired   Sample   T-Test   dan   uji N-Gain.  Multimedia Shape Fun dinilai kategori sangat layak dengan perolehan dari ahli media dan ahli materi sebesar 93,7 %. Kelayakan tersebut diperoleh karena multimedia Shape Fun berbantuan lagu memiliki tampilan yang menarik, navigasi yang mudah digunakan, serta perpaduan unsur teks, gambar, kuis interaktif, dan lagu edukasi yang sesuai dengan karakteristik peserta didik sekolah dasar. Multimedia ini efektif dengan memperoleh nilai signifikansi 0,000 dan Nilai N-gain sebesar 0,71 termasuk kategori tinggi, yang membuktikan peningkatan hasil belajar secara signifikan. Hasil tersebut menunjukkan multimedia Shape Fun berbantuan lagu sebagai inovasi media pembelajaran berbasis digital sangat layak dan efektif digunakan untuk meningkatkan hasil belajar peserta didik kelas IV pada pembelajaran matematika materi segi banyak.